Corporate governance and organizational Performance: A case of Institut Polytechnique De Byumba, Rwanda. - Bonaventure, Twagirumugabe (Kabale University, 2020)
The performance of firms and the way they are governed worldwide have attracted great deal of attention in the past decades owing to corporate failures. This study was examined the relationship between corporate governance and organizational performance. Unlike most studies on corporate governance which predominantly use only financial variables affecting governance, the study took a different approach by using non-financial variables. This combined set of variables was used for theoretical and empirical models. Based on the extended literature, the researcher developed a conceptual framework and a set of hypotheses to examine the relationship between corporate governance and organizational performance. Board characteristics considered in this research include board size, board of director role, gender diversity, and educational qualification of board members and decision making and implementation. It adopted quantitative methodological framework through which the primary data collected from a sample of 124 respondents involving 108 employees and 16 board members at IPB and were analyzed using both regression and correlation analysis techniques to find the relationship between corporate governance and organizational performance on one hand and the degree of relationship between corporate governance and organizational performance. The findings shows that large board size, board skill, management skill, longer serving, decision making and implementation are positively associated with the performance of organizations. Organizations are encouraged to adopt good corporate governance practices to improve their performance and also to protect the interest of the shareholders.